2022
DOI: 10.3390/antiox11081475
|View full text |Cite
|
Sign up to set email alerts
|

Response of Thymus lotocephalus In Vitro Cultures to Drought Stress and Role of Green Extracts in Cosmetics

Abstract: The impact of drought stress induced by polyethylene glycol (PEG) on morphological, physiological, (bio)chemical, and biological characteristics of Thymus lotocephalus López and Morales shoot cultures have been investigated, as well as the potential of iron oxide nanoparticles, salicylic acid, and methyl jasmonate (MeJA) as alleviating drought stress agents. Results showed that PEG caused oxidative stress in a dose-dependent manner, raising H2O2 levels and reducing shoots’ growth, photosynthetic pigment conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
8
1
Order By: Relevance
“…Contrary to our results, severe drought stress did not affect the accumulation of rosmarinic acid in Salvia milltiorrhiza [44]. Furthermore, PEG showed negative effects on RA accumulation in Thymus lotocephalus shoots [56]. In summary, dehydration stress appears to modulate RA biosynthesis differently in related Lamiaceae species contingent upon the severity and duration of experimental conditions.…”
Section: Content Of Phenolic Acidscontrasting
confidence: 99%
“…Contrary to our results, severe drought stress did not affect the accumulation of rosmarinic acid in Salvia milltiorrhiza [44]. Furthermore, PEG showed negative effects on RA accumulation in Thymus lotocephalus shoots [56]. In summary, dehydration stress appears to modulate RA biosynthesis differently in related Lamiaceae species contingent upon the severity and duration of experimental conditions.…”
Section: Content Of Phenolic Acidscontrasting
confidence: 99%
“…The antioxidant, anticancer, and antimicrobial properties of this class of phenolic compounds were also clearly demonstrated, their scavenging activity against different free radicals being 3−fold higher compared to industrial synthetic antioxidants. Additionally, in a study about the role of elicitation in alleviating drought stress in Thymus lotocephalus in vitro cultures, [ 35 ] found that MeJA was more effective than SA in promoting the biosynthesis of phenolic compounds (mainly phenolic acids), increasing their accumulation by up to 38.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Roots regulate water and nutrient uptake and are the first to sense water deficits ( Hein et al., 2016 ). When plants experience drought conditions, a decrease in water transport from the roots to the aboveground parts through the xylem directly signals drought stress to the plant ( Mansinhos et al., 2022 ). Roots can be traced to coordinated cell division, elongation, and differentiation events to enhance their ability to absorb water ( Rellan-Alvarez et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%